Зрощення у збірці Івана Іова "Періодична система слів" - Андрішко, О. (Культура слова, 2020)
У статті розглянуто особливості слів-зрощень у збірці
Івана Іова «Періодична система слів». У досліджуваній
книжці виділено кілька груп зрощень – слів, утворених лексико-
синтаксичним способом: на основі сурядних і підрядних
словосполук, залишкових словосполук (поєднання в одному
слові службових частин мови (найчастіше прийменника) з
повнозначними в непрямих відмінках (насамперед іменник).
У «Періодичній системі слів» також широко представлені
зрощення-паліндроми, що є рідкістю в українській поезії.
Вершиною словотвірної майстерності можна вважати
вірш, який дав назву збірці; в ньому Іван Іов показав
невичерпні можливості словотворення, що в поєднанні з
оригінальним авторським стилем дало нам яскравий зразок
експериментальної літератури. The article deals with the features of word-coalescences in the book of
Ivan Iov «Periodic system of words», which is considered to be the most
prominent in the author’s work. Ivan Iov belonged to the leading Ukrainian
avant-garde poets to the 20th-21th centuries, leaving a significant trace
both in syllabic tonic poetry and in experimental poetry (palindromes,
graphic poems, acrostic, brachicolons, logogriphs, collage etc.). Ivan Iov
was born in 1948 in the village of Kamianka, in the Apostolove District
of the Dnipro region in a large family. He graduated from Kamianets-
Podilskyi National Ivan Ohiienko University and then worked as a teacher
and journalist.
In 1997, he published his most famous and significant collection,
«The Periodic system of words», where he continued the traditions
of Ivan Velychkovskyi and which became the subject of our research.
Particular attention deserves to occasionalisms by the author. In the
research book you can identify several groups of coalescences-words,
created lexico-syntactical method, on the basis of sued and subordinate
phrases, residual phrases (most often prepositions). Also a feature of the
creation of neologisms in Ivan Iov is the use of the names and surnames
of famous people – friends of the poet, for example, Valerii Basyrov –
the editor of this book; Hryhorii Huseinov – writer, laureate of the Taras
Shevchenko National Prize; Mykola Zhulynskyi – Director of the Taras
Shevchenko Institute of Literature of NAS of Ukraine. In the «Periodic
system of words», the coalescences-palindromes (both commonly used
and occasional) are also widely represented, which is a decisive feature of
the creative manner of Ivan Iov compared with other avant-garde poets.
The top of word-formation skill can be considered the poem that gave the
collection its name; in it Ivan Iov showed the inexhaustible possibilities
of word formation, which in combination with the original author’s style
gave us a wonderful example of experimental literature.